Natural photosynthetic microboring communities produce alkalinity in seawater whereas aragonite saturation state rises up to five - Tribollet, Aline; Chauvin, Anne; Cuet, Pascale (Frontiers in Earth Science, 2022)
Bioerosion, resulting from microbioerosion or biogenic dissolution, macrobioerosion and grazing, is one the main processes involved in reef carbonate budget and functioning. On healthy reefs, most of the produced carbonates are preserved and accumulate. But in the context of global change, reefs are increasingly degraded as environmental factors such as ocean warming and acidification affect negatively reef accretion and positively bioerosion processes. The recent 2019 SROCC report suggests that if CO2 emissions in the atmosphere are not drastically reduced rapidly, 70% to 99% of coral reefs will disappear by 2100. However, to improve projections of coral reef evolution, it is important to better understand dynamics of bioerosion processes. Among those processes, it was shown recently that bioeroding microflora which actively colonize and dissolve experimental coral blocks, release significant amount of alkalinity in seawater both by day and at night under controlled conditions. It was also shown that this alkalinity production is enhanced under ocean acidification conditions (saturation state of aragonite comprised between 2 and 3.5) suggesting that reef carbonate accumulation will be even more limited in the future. To better understand the conditions of production of alkalinity in seawater by boring microflora and its possible consequences on reef resilience, we conducted a series of experiments with natural rubble maintained under natural or artificial light, and various saturation states of aragonite. We show here that biogenic dissolution of natural reef rubble colonized by microboring communities dominated by the chlorophyte Ostreobium sp., and thus the production of alkalinity in seawater, can occur under a large range of saturation states of aragonite, from 2 to 6.4 under daylight and that this production is directly correlated to the photosynthetic activity of microboring communities. We then discuss the possible implications of such paradoxical activities on reef resilience.